1991
DOI: 10.5014/ajot.45.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Falls and Fear of Falling Among Elderly Persons Living in the Community: Occupational Therapy Interventions

Abstract: Each year, about one third of the population over 65 years of age experiences at least one fall (Perry, 1982). Assessment of the incidence of falls and the prevalence, intensity, and covariates of fear of falling among community-based elderly persons was conducted through interviews of 115 residents in a housing development (mean age = 78 years). Fifty-three percent reported having fallen in recent years, 32% in the last year. Fear of falling ranked first when compared with other common fears. In a logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
141
3
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 3 publications
5
141
3
3
Order By: Relevance
“…Occupational therapy practitioners have promising preliminary evidence supporting the effectiveness of facilitating behavior change (Peterson & Murphy, 2002;Walker & Howland, 1991). The limitation in this area of research involves the use of fall risk as the identified outcome.…”
Section: Making Behavioral Changes and Reducing Fear Of Fallingmentioning
confidence: 99%
See 2 more Smart Citations
“…Occupational therapy practitioners have promising preliminary evidence supporting the effectiveness of facilitating behavior change (Peterson & Murphy, 2002;Walker & Howland, 1991). The limitation in this area of research involves the use of fall risk as the identified outcome.…”
Section: Making Behavioral Changes and Reducing Fear Of Fallingmentioning
confidence: 99%
“…Occupational therapy practitioners can facilitate behavioral changes by addressing changes in a person's routines to decrease fall risk and fear of falling (e.g., instructing older adults to use stair railings consistently; Peterson & Clemson, 2008). Additionally, behavioral interventions may be incorporated into multifactorial interventions such as home modifications and home safety education (AGS & BGS, 2010;Walker & Howland, 1991), exercises (Harling & Simpson, 2008), assertiveness training (Walker & Howland, 1991;Zijlstra et al, 2009), self-efficacy training (e.g., Cheal & Clemson, 2001;Zijlstra et al, 2009), and multicomponent interventions that address fear of falling such as A Matter of Balance (Peterson & Clemson, 2008) and Stepping On (Clemson et al, 2004;Peterson & Clemson, 2008). Occupational therapy practitioners can also reduce fear of falling in older adults by having them practice fear-provoking daily tasks to increase confidence, assisting them with cognitive restructuring (Peterson & Murphy, 2002;Zijlstra et al, 2009), and using guided imagery (Juarbe & Bondoc, 2009).…”
Section: Making Behavioral Changes and Reducing Fear Of Fallingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Walker and Howland, fear of falling can compromise quality of life among elderly persons by diminishing the sense of well being, limiting mobility, and reducing social interaction. Fear of falling becomes a risk factor for falls due to decreased movement and reduced physical conditioning [11]. Walker and Howland reported that fear of falling appeared to contribute to reduced activity independent of other risk factors.…”
Section: Influence Of Fear Of Fall On Spatial and Temporal Parametersmentioning
confidence: 99%
“…Walker and Howland reported that fear of falling appeared to contribute to reduced activity independent of other risk factors. According to several studies, falling and fear of falling are highly correlated [10][11][12]. Fear of falling can also affect the gait parameters of a person [13,14].…”
Section: Influence Of Fear Of Fall On Spatial and Temporal Parametersmentioning
confidence: 99%